Unconscionability in the Law and Practice of Franchising - Mohd Ishan, Zahira (2008)
This study examined the operation of unconscionability in the law of franchising and the nature of existence of unconscionability in practice of franchising. Franchising is relatively a new branch of commercial law and practically opened to various forms of abuses by the franchisors and franchisees. Meanwhile, unconscionability has a rather uncertain scope within the general sphere of contract law. It is therefore, important to also identify the true nature of franchising, the development of unconscionability and its relationship with the relevant contractual theories and other doctrines or notions, the probabilities of unconscionable practices in franchising and the totality of the whole spectrum of the idea of unconscionability from the legal perspectives. Applying the qualitative approach by means of inductive reasoning using the historical research method, this study found that franchising resulted from the commercial practices or conveniences rather than any legal tradition. It is multidimensional in nature, which incorporates, among other, the concept of contract law, a notion of licence and some features of usufruct. Unconscionability is the most proper doctrine to deal with the abuses and unfair practices that occur in franchising. In fact, there are probable occurrences of unconscionable practices in franchising in Malaysia based on the empirical studies of actual cases. As unconscionability is still evolving and the formulation of another parameter could still be contemplated, a new parameter is proposed in this research whereby the broad doctrine of unconscionability encompasses fairness, good faith, fair dealing and undue influence, while inequality of bargaining power and honesty in certain circumstances become the supporting factors in proving unconscionability. From this research, it is concluded that unconscionability is the situation whereby the contract is entered into, negotiated and obtained. As the contract is a bargain, when the bargain is unconscionable it becomes unconscionable bargain. Unconscionability is an essential doctrine in the law of contract and the formulation of the new parameters of unconscionability in the contract law is also applicable to the law of franchising. The parameters can assist in promoting conscionability in the franchise business environment locally and internationally.